Empowering Bulota Village Communities through Lake Limboto Water Quality Monitoring - Dewi Diana Paramata; Mulyani Zahra Paramata (Universitas Negeri Gorontalo, 2026)
Lake Limboto is a strategic freshwater ecosystem in Gorontalo Province whose declining water quality, driven by sedimentation, water hyacinth proliferation, and domestic waste, threatens fisheries productivity and the welfare of surrounding communities, particularly in Bulota Village, Telaga Jaya District. Coastal residents in this area have limited knowledge and technical capacity to monitor water quality independently. This community engagement program therefore aimed to build local capacity for participatory water quality monitoring and to strengthen blue economy literacy. Activities included a preliminary field survey, coordination with the village government, technical training and field practice in measuring pH, Total Dissolved Solids (TDS), and Dissolved Oxygen (DO), formation of a village monitoring group, and development of manual and digital logbooks. Measurements at three observation stations around Lake Limboto showed pH, TDS, and DO values within the Class III water quality standard for fisheries. Participants gained the ability to operate simple monitoring instruments and record data systematically, and a village-based monitoring group was established as an institutional foundation for continued, community-driven monitoring. Community empowerment through participatory water quality monitoring and blue economy literacy is therefore an effective strategy for supporting the long-term sustainability of Lake Limboto and the welfare of its coastal communities.